Clinical efficacy of avatrombopag and recombinant human thrombopoietin in the treatment of chronic liver disease-associated severe thrombocytopenia: A real-world study - Wang, Yong-Shuai; Wang, Wei; Zhang, Sai; Zhang, Shen-Yu; Shen, Ai-Zong; Wang, Wei; Song, Hua-Chuan; Yao, Huan-Zhang; Song, Rui-Peng; Meng, Fan-Zheng; Li, Lei; Nashan, Bjoern; et al. (Frontiers in Pharmacology, 2022)
Abstract Purpose: To investigate the clinical efficacy of avatrombopag an oral thrombopoietin receptor agonist versus intramuscular recombinant human thrombopoietin (rh-TPO) in the treatment of severe thrombocytopenia (TCP) associated with chronic liver disease (CLD). Methods: The clinical data including 250 patients with severe TCP associated with CLD were collected in a single hospital from January 2019 to January 2022. The main observation indicators were therapeutic response rate, the changes of platelet (PLT) and adverse events. Propensity score matching (PSM) was used to adjust the baseline variables. Results: After PSM, a total of 154 patients were collected in the avatrombopag group and rh-TPO group, including 77 patients in each group. There was no statistically significant difference between the two groups in the effect of increasing PLT count (Waldχ2 =1.704, P =0.192; Waldχ2 =0.220, P =0.639). Meanwhile, no interaction between time and different medications was found (Waldχ2 =0.631, P =0.889; Waldχ2 =1.273, P =0.736). Interestingly, in the subgroup analysis, both before and after PSM, avatrombopag showed better clinical efficacy than rh-TPO in the treatment of TCP associated with CLD in Child-Pugh Class A (88.89% vs. 63.41%, P =0.003; 81.33% vs. 61.76%, P =0.043). Much less patients reported dizziness in avatrombopag group than in rh-TPO group both before and after PSM (7.8% vs. 25.0%; 7.8% vs. 24.7%, P <0.05). Conclusion: Both before and after PSM, avatrombopag showed better clinical efficacy than rh-TPO in the treatment of TCP associated with CLD in Child-Pugh Class A and showed lower incidence of dizziness in all patients.